Answer: x = 0
Step-by-step explanation:
4x − 3 + x = 7x − 3
Step 1: Simplify both sides of the equation.
4x − 3 + x = 7x − 3
4x + −3 + x = 7x + −3
(4x + x) + (−3) = 7x − 3(Combine Like Terms)
5x + −3 = 7x − 3
5x − 3 = 7x − 3
Step 2: Subtract 7x from both sides.
5x − 3 − 7x = 7x − 3 − 7x
−2x − 3 = −3
Step 3: Add 3 to both sides.
−2x − 3 + 3 = −3 + 3
−2x = 0
Step 4: Divide both sides by -2.
-2x/-2 = 0/-2
x = 0
D is a function because there are no repeated x values
for example b is not a function because we have (0,-7) and (0,-9)
Answer:
To construct the Square using a compass and straight edge, you have written the steps not in proper order. I am rearranging the steps for you
1. Construct horizontal H J¯¯¯¯¯
2. Construct a circle with point H as the center and a circle with point J as a center with each circle having radius HJ .
3.Label the point of intersection of the two circles above HJ¯¯¯¯¯ , point K, and the point of intersection of the two circles below HJ¯¯¯¯¯ , point L.
4.Construct KL¯¯¯¯¯ , the perpendicular bisector of HJ¯¯¯¯¯ , intersecting HJ¯¯¯¯¯ at point M.
5.Construct a circle with point M as the center with radius MJ .
6.Label the point of intersection of circle M and KL¯¯¯¯¯ closest to point K, point N, and the point of intersection of circle M and KL¯¯¯¯¯ closest to point L, point O.
7.Construct HN¯¯¯¯¯¯ , NJ¯¯¯¯¯ , JO¯¯¯¯¯ , and OH¯¯¯¯¯¯ to complete square HNJO .
Answer
B
Step-by-step explanation:
$58-$25=x this would be the equation i believe